Numerical investigations on oscillating aspirations controlling separation flows in linear highly loaded compressor cascades - Liu, Bao; Cai, Le; Xu, Hao; Fu, Haiyan; Wang, Songtao (Frontiers in Energy Research, 2022)
The effect of boundary layer oscillating suction (BLOS) on the vortex structure of high-load linear compressor cascades is studied by a high-fidelity numerical calculation. The oscillation parameters (amplitude and frequency) and suction control parameters (suction position and mass flow) are continuously adjusted. It was found that higher aerodynamic efficiency could be obtained with suitable oscillation parameters and suction control parameters. This is achieved because BLOS not only absorbs the low-energy fluid in the boundary layer but also optimizes the vortex structure in the compressor passage.